VIDEOCAPSULAR EXAMINATIONS IN PEDIATRICS. THE HISTORY OF DEVELOPMENT AND USE - P.L. Shcherbakov; M.M. Lokhmatov ("Paediatrician" Publishers LLC, 2006)
The article is dedicated to the history and making of videocapsular endoscopy world wide and in Russia. The working principles of the videocapsule and all system of video capsular endoscopy are described. Indications and contraindications to its application are defined. Analysis of information value of videocapsular endoscopy is carried out as compared to other kinds of visual diagnostic methods of examination of digestive organs. Specific clinical examples showing the effectiveness of performing of videocapsular endoscopy are given.Key words: videocapsular endoscopy, diagnostics, gastroin testinal tract pathology, children.